Inhomogeneous dealloying kinetics along grain boundaries during liquid metal dealloying. (20th April 2022) - Joo, S.-H.; Jeong, Y.B.; Wada, T.; Okulov, I.V.; Kato, H.
Highlights: l Temperature increase enhances the inhomogeneous Mg melt wetting of the Fe50 Ni50 +Mg. l Energy of GBs is the key factor defining the occurrence of inhomogeneous dealloying. l Stable twin boundary hardly reacts with the Mg melt. l Minor addition of alloying elements strongly affects the inhomogeneous dealloying. Abstract: In this study, the inhomogeneous dealloying phenomenon during the liquid metal dealloying (LMD) was investigated using Fe50 Ni50 +Mg and (FeCo)50 Ni50 +Mg systems. For the Fe50 Ni50 +Mg system, the inhomogeneous dealloying and wetting of Mg melt occurred along triple junction (TJ) and grain boundary (GB). Temperature increase enhances the inhomogeneous dealloying kinetics and leads to the formation of the plate-shaped abnormal ligaments at the GB region. The energy banlance between a GB energy (γGB ) and solid-liquid interface energies (γsl ) is the key factor governing the inhomogeneous dealloying and wetting. Particularly, the low-energy twin boundaries were unaffected by the inhomogeneous dealloying. Therefore, precursor microstructure is an important factor determining the final morphology of dealloyed material as well as its physical properties. In the case of the (FeCo)50 Ni50  precursor, all TJ and GB were stable against the preferred penetration of Mg melt from 600 °C to 800 °C. It was concluded that a minor addition of alloying elements (V or Cr) changes GB characteristics as well as γsl of the precursor alloy. Consequently, this significantly influences dealloying mechanisms and final morphology of the dealloyed material. The current findings demonstrate the importance of GB engineering in the precursor materials for the technological application of liquid metal dealloying for the synthesis of advanced structural and functional materials. Graphical abstract: Image, graphical abstract .